Merger Waves and Firm Growth: Contemporary Historical Evidence. (5th February 2013) - Majumdar, Sumit K.; Moussawi, Rabih; Yaylacicegi, Ulku
ABSTRACT This article presents the outcomes of an evaluation of the impact of the series of mergers of the local exchange companies that have taken place between 1988 and 2001 on an important measure of performance of the firms undergoing the mergers. The analysis reveals that after firms have undertaken one merger they experience little or no growth after such mergers, but the impact of second mergers on firm growth have been negative. If an important motive in undertaking mergers has been to enhance firm growth, then the merger waves that have been approved and consummated have led to performance declines. The impacts of the merger wave on the growth of the telecommunications sector firms have been negative.